FACTORS CONTRIBUTING TO INCREASED CASES OF TYPHOID FEVER AMONG PATIENTS AGED 15-45 YEARS IN SOROTI REGIONAL REFERRAL HOSPITAL, SOROTI DISTRICT. A CROSS-SECTIONAL STUDY. - Arapu, Denis; Mubangizi, Prosper (Student's Journal of Health Research Africa, 2023)
Background: This study aimed to determine the factors contributing to increased cases of typhoid fever among patients aged 15-45 years in Soroti Regional Referral Hospital, Soroti District. Methodology: A descriptive study design employed both qualitative and quantitative data collection, a simple random sampling technique was used. Results: The majority of respondents 85% had heard of typhoid fever, 52% did not complete treatment for typhoid when they fell sick, 64% of them did not have latrines, and out of the few with them 84% did not have latrines covers and 52% do not know what contaminates water in their community. 42% get their water from the tap, 58% dispose of their wastes in their backyards of homes, 40% eat food from their homes, they do not follow proper hygienic methods of food handling, and 70% do not treat or boil drinking water. half 50% of the respondents move long distances to seek medical services. Conclusion: Most people do not complete their treatment for typhoid fever, do not know how typhoid fever is transmitted from one person to another, that there is management of waste, and food, do not boil water for drinking, the majority do not have latrines, move long distances to seek health services, the health facility does not have required laboratory equipment’s to facilitate routine typhoid testing and diagnosis, and gaps in the general examination of patients were discovered. Recommendations : Uganda National Water and Sewerage Corporation should improve water supply and treatment, sensitize people on how to prevent communicable diseases through the Centre Disease Control and Prevention through the Ministry of Health and more health workers should be recruited to improve service delivery. People in the community should be encouraged to boil water before drinking and routine of the health facility for general body checkups.